Chaihushugan powder regulates the gut microbiota to alleviate mitochondrial oxidative stress in the gastric tissues of rats with functional dyspepsia - Liu, Xuejiao; Yang, Keming; Jia, Yuebo; Yeertai, Yeliya; Wu, Chenheng; Wang, Xiangxiang; Jia, Qingling; Gu, Zhijian; Cong, Jun; Ling, Jianghong (Frontiers in Immunology, 2025)
IntroductionFunctional dyspepsia (FD) is a prevalent functional gastrointestinal disorder associated with oxidative stress (OS) and dysbiosis. Chaihushugan powder (CHSGP) demonstrates efficacy in treating FD; however, the underlying therapeutic mechanism is not yet elucidated. This study aims to investigate the effects of CHSGP on OS and gut microbiota (GM) in FD rats, with a particular emphasis on the role of GM as a potential target for the antioxidant properties of CHSGP.MethodsThe FD rat model was established with a modified tail-clamp stimulation and the administration of the CHSGP decoction at a dosage of 9.6 g/kg via gavage for a duration of 4 weeks. The GM was depleted by the administration of a cocktail of metronidazole (200 mg/kg), ampicillin (200 mg/kg), neomycin sulfate (200 mg/kg), and vancomycin (100 mg/kg). Fecal microbiota transplantation (FMT) was performed with CHSGP-treated fecal supernatant at a dosage of 10 mL/kg. The gastrointestinal motility was measured using the rates of gastric emptying and small intestine propulsion. Hematoxylin and eosin staining was employed to elucidate the pathological changes, while the transmission electron microscope was used to examine the microstructures of the interstitial cells of Cajal (ICC). Chemiluminescence, colorimetric assay, immunofluorescence co-staining, and western blot assay were employed to identify the OS-related markers (ROS, SOD, NOX4, PRDX1, and TRX2). Sequencing of fecal microbiota was performed utilizing 16S rDNA.ResultsThe CHSGP decoction promoted gastrointestinal motility, protected the microstructure of ICC, and reduced OS in FD rats. The GM composition was also regulated by CHSGP. However, these effects disappeared after microbiota depletion. Fortunately, the FMT therapy reinstated them.ConclusionChaihushugan powder decoction might regulate the GM to alleviate mitochondrial OS in the gastric tissues of FD rats.